Cataract surgery in neovascular AMD: impact on visual acuity and disease activity - Hin Yan Tang; Mats Rosén; Elisabet Granstam (BMC Ophthalmology, 2023)
Abstract Background Cataract and neovascular age-related macular degeneration (nAMD) often co-exist and both contribute to impaired vision. It has been debated whether cataract surgery can increase nAMD activity. The purpose of this retrospective study was to investigate the impact of cataract surgery on visual acuity, treatment intensity for nAMD and macular morphology in patients with on-going treatment for nAMD. Methods Data was obtained from the Swedish Macular Register, the Swedish National Cataract Register, optical coherence tomography (OCT) images and patient charts. All eyes were treated at the Department of Ophthalmology at the County Hospital of Västmanland, Västerås, Sweden. Follow-up was 6 months after surgery. The study was approved by the Swedish Ethical Review Authority. Results In total, 156 patients (168 eyes) were included. The mean age at cataract surgery was 82 (standard deviation, SD 6) years. Both distance and near visual acuity improved after surgery. Distance visual acuity increased from 59 (SD 12) to 66 (SD 15) letters ETDRS (P < 0.001). Proportion of eyes with normal near visual acuity increased from 12 to 41%. The anti-vascular endothelial growth factor (VEGF) treatment intensity remained unchanged: mean of 3.4 (SD 1.9) and 3.3 (SD 1.7) treatments were given 6 months pre- and postoperatively, respectively. The prevalence of intraretinal fluid (IRF) in the macula increased from 22 to 31% postoperatively, while subretinal fluid, fluid under the pigment epithelium (sub-RPE fluid) and central retinal thickness were unaltered. In eyes with new IRF, improvement in visual acuity and number of anti-VEGF treatments were similar to eyes without new IRF. Conclusion Cataract surgery improved visual acuity in patients with on-going treatment for nAMD and did not affect anti-VEGF treatment intensity. Macular morphology remained unchanged. The slight increase in intraretinal fluid after surgery was not found to affect visual acuity or anti-VEGF treatment intensity. It is hypothesized that this might indicate that it represents degenerative intraretinal cystic fluid.